APPLICATION OF TREND ANALYSIS AS A MEANS TO OBSERVE FINANCIAL PERFORMANCE AT PT SIANTAR TOP TBK - Ranti Melasari; Suryani; Rosliana; Rahman, Said muhammad aulia rahman; Hidayatul Fitri; Tiara Suci Lestari; Muhammad Agis (Indragiri Research Center (ingreat), 2024)
This research discusses the application of trend analysis to observe the financial performance of PT Siantar Top Tbk from 2018 to 2023. The research objective is to analyze the company's financial performance using the trend analysis method, with a focus on net income. Data was obtained from internal company records during that period. The results of the analysis show that the company's net income tends to decrease from 2018 to 2023, although it has increased from year to year but has decreased in 2023. Financial trend analysis also shows an increase in cost of revenue, gross profit and net profit from year to year, but there was a decrease in net profit in 2020-2021. Good financial management is needed to manage company funds well in order to maximize profits, reduce risks, maintain cash flow, and satisfy shareholders. Financial statement analysis, including trend analysis, is important for assessing company performance and making investment decisions based on historical data.